Development of a low cost laser scanning system for gear repair using additive manufacturing technologies - Pang, Wee Ching (2018)
Measurement and dimensioning is the primary purpose of the pre-processing stage in many generalized strategies for parts repair/remanufacturing. This work reports on a low cost system for the dimensioning of worn out parts. The system consists of both mechanical element made up of a Hokuyo URG-04LX-UG01 2D scanning laser rangefinder and a rotating mechanism actuated by a Dynamixel MX-28 servomotor and consolidated software element integrating motion control and point cloud generation. A case study involving the scanning of a rack is reported.